2022
DOI: 10.1101/2022.11.14.516464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age and Sex-Dependent Differences in Human Cardiac Matrix-Bound Exosomes Modulate Fibrosis through Synergistic miRNA Effects

Abstract: Aging is a risk factor for cardiovascular disease, the leading cause of death worldwide. Cardiac fibrosis is a harmful result of repeated myocardial infarction that increases risk of morbidity and future injury. Interestingly, rates of cardiac fibrosis are different between young and aged individuals, as well as men and women. Here, for the first time, we identify and isolate matrix-bound extracellular vesicles from the left ventricles (LVs) of young or aged men and women. These LV vesicles (LVVs) show differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 86 publications
(143 reference statements)
0
14
0
Order By: Relevance
“…We found that breast MBVs isolated from aged mice were around 140 nm whereas those isolated from young mice were 160 nm. While this difference is fairly small, previous studies from our group have shown that heart tissue MBVs isolated from aged human donors are smaller than those isolated from young donors, indicating that the size difference may not be tissue specific, but age specific 36 . This also aligns with the results from another study showing that the circulating EVs isolated from the plasma of aged mice were smaller in size than those from young mice 51 , supporting the claim that this size difference may be aging-related.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We found that breast MBVs isolated from aged mice were around 140 nm whereas those isolated from young mice were 160 nm. While this difference is fairly small, previous studies from our group have shown that heart tissue MBVs isolated from aged human donors are smaller than those isolated from young donors, indicating that the size difference may not be tissue specific, but age specific 36 . This also aligns with the results from another study showing that the circulating EVs isolated from the plasma of aged mice were smaller in size than those from young mice 51 , supporting the claim that this size difference may be aging-related.…”
Section: Discussionmentioning
confidence: 53%
“…However, more recent studies shed light on an unconventional subgroup of EVs, termed matrix vesicles or matrix bound vesicles (MBVs), which are embedded within the ECM and could only be isolated through enzymatic digestion. Previous studies in a few different tissues (bladder, small intestinal submucosa, heart, and dermis) 35,36,37 confirmed the presence of these MBVs, and the effects of these MBVs and their small RNA cargos on regulating the cell behavior, including macrophage phenotype 38 , cell axon growth 39 , and disease progression 40 . Although MBVs have been discovered in studies with other tissues and organs, to date, no research has been done on breast ECM bound MBVs and their influence on breast cancer.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Other components of the heart ECM are laminin, fibronectin, elastin, fibrillin 1, and heparan sulfate proteoglycans [95,97,98] (table 2). Moreover, ECM is a reservoir for anchored signaling molecules including the GFs, cytokines, proteases, and noncoding RNAs such as miRNAs and long noncoding (ln) RNAs [97,[99][100][101].…”
Section: Heart Extracellular Matrixmentioning
confidence: 99%
“…[20] In a more recent study, MBVs were isolated from human left ventricles ECM of young or aged men and women, and the data indicated that synergistic effects of miR-NAs from matrix-resident exosomes may influence the differential clinical response to myocardial infarction. [21] However, most studies generated MBVs from animal or human tissues. Human tissues are a limited resource, while animalderived MBVs raise safety concerns for clinical purposes.…”
Section: Introductionmentioning
confidence: 99%